The Relationship between Abdominal Muscle Strength and Jump Service Skills in Volleyball Extracurricular at SMKN 06 Mukomuko Regency - Baruno Tri Pamungkas; Mesterjon Mesterjon; Mariska Febrianti (Penerbit Jurnal Indonesia, 2021)
This study aims to find out how the UAS questions in physical education lessons are made by sports teachers at SMP Negeri 3 Bengkulu Tengah. This research is a qualitative research. The subjects in this study were sports teachers who made UAS questions in class VII. The instruments in this research are content validity test instruments and construct validity tests. The results of the study show that the questions made by the sports teacher at SMP Negeri 3 in Central Bengkulu have not been said to be good. Because the teacher is not consistent in making questions for example in the content validity test. It says on the lattice that the questions contained in the indicators are 10 but in fact only 5 items are contained in the indicators, and it is also said on the lattice of questions that are contained in the indicators from No. 1-10 while in fact on the questions of No. 26 – 30 . on the items that are not contained in the lattice indicators totaling 25 items. Analysis of the questions on the construct validity test on the rules of writing a good question at No. 14 which contains each question must use language that is in accordance with the Indonesian language rules. In the problems analyzed, the researchers found that the writing of foreign language words was not italicized.